2020
DOI: 10.1021/acs.analchem.0c01613
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Sensitive, Accurate, and Automated Single-Cell RNA Sequencing Platform with Digital Microfluidics

Abstract: Single-cell RNA sequencing (scRNA-seq) is a powerful method in investigating single-cell heterogeneity to reveal rare cells, identify cell subpopulations, and construct a cell atlas. Conventional benchtop methods for scRNA-seq, including multistep operations, are labor intensive, reaction inefficient, contamination prone, and reagent consuming. Here we report a digital microfluidics-based single-cell RNA sequencing (digital-RNA-seq) for simple, efficient, and low-cost single-cell mRNA measurements. Digital-RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 41 publications
0
46
0
Order By: Relevance
“…Conventional quantitative measurements of miRNAs expression in bulk analysis only study the average gene expression levels from a large number of cells, [16][17][18] which covers cellular heterogeneity. 19,20 Therefore, the simultaneous quanti-cation of multi-miRNAs expression in single cells is very important for cell subtypes discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional quantitative measurements of miRNAs expression in bulk analysis only study the average gene expression levels from a large number of cells, [16][17][18] which covers cellular heterogeneity. 19,20 Therefore, the simultaneous quanti-cation of multi-miRNAs expression in single cells is very important for cell subtypes discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…Although several commercial platforms are available, improvements and new approaches are still being published. Xu et al reported a digital microfluidics platform for single-cell mRNA sequencing . In digital microfluidics, researchers move around aqueous droplets in a minute, oil-filled space between two parallel plates.…”
Section: Microfluidicsmentioning
confidence: 99%
“…To the best of our knowledge, the obtained accuracy is better than the accuracy of a single‐cell DNA sequencing (which is not exceeding 80% [ 25 ] ) and close to single‐cell RNA sequencing methods (accuracy ≈96% [ 26-28 ] ). It is definitely premature to compare the well‐established single RNA and DNA sequencing with the results of this study.…”
Section: Introductionmentioning
confidence: 99%